Analisis Tematik Evaluasi Pembelajaran Berdiferensiasi dalam Hadits Tarbawi untuk Asesmen Kurikulum Merdeka - Aji Sentosa; Romlah Abubakar Askar; Miftahuddin; Muhammad Ihsan Mubarok (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study analyzes the principles of differentiated learning evaluation in tarbawi hadith and contextualizes them into the Merdeka Curriculum assessment. Given the GAP between the expectations of the Merdeka Curriculum and the uniform assessment methods still applied by Islamic Religious Education (PAI) teachers, this research employs Tomlinson's differentiation theory covering four dimensions: content, process, product, and learning environment. It uses a qualitative approach through library research and thematic hadith analysis. The findings identify and map seven authentic (sahih/hasan) hadiths into the four dimensions: content differentiation (HR. Bukhari No. 757) through diagnostic assessment and simplification of essential material; process differentiation (HR. Abu Dawud No. 495, HR. Bukhari No. 62) by adapting strategies according to age and psychological conditions; product differentiation (HR. Muslim No. 818) by appreciating various ways of demonstrating understanding; and learning environment differentiation (HR. Bukhari No. 6125) through non-stressful and supportive assessment. The contribution of this research is to formulate a differentiated evaluation framework based on hadith as a philosophical and pedagogical foundation for PAI teachers.